2013
DOI: 10.1021/jp305557s
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Gramicidin Channel Transport and Structure

Abstract: The gramicidin dipeptide is a small, cation-selective ion channel. Recent experiments have indicated that gramicidin can conduct ions at elevated temperatures. Since gramicidin is an efficient proton conductor, it is possible that this channel may have applications in fuel cell technology. In this study, we examine the temperature dependence of gramicidin A channel transport and structure with molecular dynamics simulations. In particular, the potentials of mean force (PMFs) for potassium ion motion through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 80 publications
1
7
0
Order By: Relevance
“…In the case of K + , two outer and inner cation‐binding sites are observed near the pore entrance at | z | = 12 Å and | z | = 9 Å, respectively. The positions of the cation‐binding sites observed in AMOEBA are consistent with the experimental observation and previously calculated results . In the case of Na + , the deeper binding site is observed in | z | = 9 Å.…”
Section: Amoebea Force Fieldsupporting
confidence: 90%
See 2 more Smart Citations
“…In the case of K + , two outer and inner cation‐binding sites are observed near the pore entrance at | z | = 12 Å and | z | = 9 Å, respectively. The positions of the cation‐binding sites observed in AMOEBA are consistent with the experimental observation and previously calculated results . In the case of Na + , the deeper binding site is observed in | z | = 9 Å.…”
Section: Amoebea Force Fieldsupporting
confidence: 90%
“…The single channel conductance is overestimated by several orders of magnitude compared to the experiment observation, depending on the additive force field and MD simulation protocol used. For example, previous calculated PMF for K + permeation using the additive force field demonstrated an unexpectedly high free energy barrier of 10−20 kcal/mol, whereas the experimental data indicated that the K + permeates through the gA channel with a small free energy barrier . On the other hand, Sandeep and co‐workers used the charge equilibration polarizable force field to evaluate the PMF for K + permeation in the gA channel within a small 20 DMPC bilayer …”
Section: Amoebea Force Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…One dimensional (1D) water chains/water wires and the design of their synthetic hosts attract enormous research interest owing to their key roles in fundamental biological processes [36][37][38][39] exemplified by the selective transport of water across cells in protein aquaporins, [40][41][42][43][44][45] and the transport of protons in Gramicidin A membrane channels, [46][47][48][49][50] cytochrome oxidase, [51][52][53][54][55][56] and bacteriorhodopsin. [57][58][59] The probable role of water in protein folding 60,61 and the correlation of water pathways to the activation of G-coupled receptors 62 all point towards the topical interest in water channels.…”
Section: D Water Chainsmentioning
confidence: 99%
“…The free energy profiles of K + and Na + permeating through the gramicidin A channel embedded in DMPC are characterized by our group with using the AMOEBA polarizable force field by our group [ 36 ]. The previous calculated potential mean forces (PMF) for K + permeation using the additive force field demonstrated an unexpectedly high free energy barrier of 10–20 kcal/mol [ 18 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], whereas the experimental data indicated that the K + permeates through the gA channel with a small free energy barrier [ 49 , 50 ]. Compared with the results produced by additive force field, the free energy barriers for K + /Na + through gA channel are significantly decreased [ 36 ], which are depended on the explicitly described polarization effects in AMOEBA.…”
Section: Introductionmentioning
confidence: 99%